Identification of parasites in goatfish (Upeneus sp.) sold at Asem Traditional Market, Surabaya, Indonesia - Suhartono, Sabrina B.; Sidarta, Fara S.R.; Ambarwati, Reni; Dewi, Kartika (Jurnal Biologi Papua, 2026)
Goatfish (Upeneus sp.) is a marine fish commonly sold in traditional markets and widely consumed by the community. However, fish sold in markets may carry parasites that can potentially pose health risks to consumers. Therefore, parasite identification is necessary to provide information regarding parasite occurrence in marketed fish. In this study, eight goatfish samples obtained from the Asem Traditional Market, Surabaya, Indonesia, were examined using macroscopic and microscopic methods. The results showed that 37.5% of the samples were infected with Anisakis sp., with a total of 15 larvae and an average intensity of five larvae per infected fish. The larvae were found in the digestive organs and exhibited distinctive morphological characteristics, including a boring tooth on the anterior end and a mucron on the posterior end, which support the parasite’s invasive ability. These findings indicate a potential health risk to consumers, particularly if the fish is consumed raw or undercooked. Prevention can be achieved through proper post-harvest handling and adequate cooking temperatures to ensure the larvae become non-infective.